Surgical Treatment of Lumbar Spinal Canal Stenosis by Laminectomy and Posterolateral Fusion - Mahmoud Gamal Ebrahim (Al-Azhar University, Faculty of Medicine (Damietta), 2020)
Background: Lumbar spinal stenosis is a common spinal disease, which lead to neural compression leading to pain, limitation of individuals function and reduced the quality of life.  Aim of the work:To evaluate the results of surgical treatment of lumbar spinal canal stenosis [LCS] by laminectomy and instrumented posterolateral Fusion. Patients and Methods: A prospective study had been conducted at Orthopedic Surgery Department [Al-Azhar University Hospital, Damietta] to evaluate the outcomes of treatment of lumbar canal stenosis by laminectomy and posterolateral fusion. This study included 15 patients, and the average follow up was 6 months from December 2018 to May 2019. Pain, clinical and radiological outcomes had been assessed. Preoperatively, all patients had been evaluated clinical and radiologically. In addition, lab investigations had been performed to assess the patient. Results: The study included 15 patients [10 females and 5 males], their age ranged between 30-55 years [mean age 42.8 years]. The surgical outcome [according to Odom Criteria] revealed that, excellent outcome reported among 26.7%, and 40% had good outcome, fair outcome among 26.7% and poor outcome among 6.7%. Conclusion: Laminectomy with instrumented posterolateral fusion is a good surgery to treat degenerative lumbar canal stenosis, with reasonable outcome.